Principal Leadership Based on Local Wisdom in Developing Quality Culture at SD Negeri Banjarsari 5 Serang City - Rohyadi, Edi; Yuhana, Yuyu; Atikah, Cucu (FKIP - Universitas Riau, 2025)
This study was motivated by concerns about the low literacy levels of elementary school students and the weakening of national character values among students. The purpose of this study was to analyze the leadership of the principal of SD Negeri Banjarsari 5 Kota Serang in developing a culture of quality based on local wisdom. The approach used in this study was a qualitative approach with a case study method. This method was used to explore in depth the role of the principal in applying local wisdom values as a leadership strategy, identifying leadership characteristics, and the form of quality culture implemented in the school. Data was collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion techniques. The results of the study indicate that school leadership based on local wisdom significantly contributes to building a culture of quality in schools. School principals apply local values such as togetherness, mutual cooperation, religiosity, exemplary behavior, and discipline as the foundation for school management. This study concludes that school leadership that integrates local wisdom is capable of creating a school environment conducive to the development of a quality culture in elementary schools.